2020
DOI: 10.1038/s41598-020-63888-7
|View full text |Cite
|
Sign up to set email alerts
|

The optimal spatial noise for continuous flash suppression masking is pink

Abstract: Recently, the methodology of CFS and in particular the type of mask used to achieve suppression has been the subject of some attention, with studies addressing both temporal 19,20,22 and spatial aspects 19,23 of CFS masking. However, it is not clear from those results whether spatial density in general, or more specifically the number of edges, influenced the effectiveness of the masking. To investigate this question, we created a set of masks that vary in spatial density, but do not contain edges as would be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 39 publications
1
21
0
Order By: Relevance
“…They show, along with other recent findings, that routine experimental procedures such as contrast normalisation can have facilitatory effects on stimulus salience 37 , 50 . Moreover, they contribute to current and developing discussions regarding the mechanisms of b. CFS, its reliability as a measure of conscious visual processing 23 , 24 , 26 29 , 38 , 51 , in showing that stimulus visibility under b. CFS also varies according to the contrast content of face stimuli, and the implications this has for our understanding of perceptual biases for emotional expressions.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…They show, along with other recent findings, that routine experimental procedures such as contrast normalisation can have facilitatory effects on stimulus salience 37 , 50 . Moreover, they contribute to current and developing discussions regarding the mechanisms of b. CFS, its reliability as a measure of conscious visual processing 23 , 24 , 26 29 , 38 , 51 , in showing that stimulus visibility under b. CFS also varies according to the contrast content of face stimuli, and the implications this has for our understanding of perceptual biases for emotional expressions.…”
Section: Discussionmentioning
confidence: 92%
“…Cumulative evidence shows that suppression strength varies according to multiple factors under b. CFS, including the spatial and temporal properties of target and mask stimuli. For example, findings show that the suppression strength of b. CFS masks are strongest temporal frequencies below that of 10 Hz that is typically used 26,27 , when target stimuli and masks are matched for temporal frequency 28 , and also according the spatial noise used to create masks 29 .…”
mentioning
confidence: 99%
“…Unlike previous research in conventional binocular rivalry settings, we used random noise-based masks rather than sinusoidal patterns. Pink noise (1/F frequency characteristics) stimuli have been shown to be an optimal noise for CFS 29 , however they do not have an orientational preference and can therefore not be set in relative alignment to the target orientation. We thus modi ed pink noise stimuli by applying an orientation bandpass to the noise characteristics, allowing for a strong directional tuning of the noise while otherwise maintaining the randomness of the appearance (see Methods below).…”
Section: Experiments 1: Luminancementioning
confidence: 99%
“…Further investigation of different kinds of random noise for CFS masking found that spatial pink noise (1/F noise) achieved the longest suppression duration compared to other random noises 29 . Other features and specially constructed masks have also received some recent attention [30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…Using noise to mask a given image characteristic allows specifying whether this characteristic is processed independently [21,22] and has been used to investigate unconscious visual processing [23,24] or to an applied machine learning approach to psychophysical studies of second-order visual processing [25].…”
Section: Introductionmentioning
confidence: 99%